(untitled) (Communications in Computational Physics, 2021)
Drag correlations are very important in particle-laden two-phase flow simulations. Some statistical studies have investigated extracting particle configuration factors from simulation data to improve drag correlations. However, little attention has been paid to studying particle configuration effects on drag from the perspective of the flow mechanism. In this paper, a direct numerical simulation (DNS) method based on the second-order accurate immersion interface method is developed to provide highly reliable data. Then, the 'shielding' effect of the two-particle configuration on drag is comprehensively analysed under different angles, distances, and Reynolds number (Re) values, revealing that the complex configuration dependence of the drag influence is attributed to the dominant flow mechanism, such as the 'pressure region unit', 'nozzle', and 'wake' effects. Moreover, we study the 'superposition' effect of the three-particle configuration on drag in a finite Re range. The results show that when the surrounding particles do not directly shield each other, the drag influence calculated by pairwise linear superposition is close to the drag influence revealed by DNS. Otherwise, when the shielding phenomenon of the surrounding particles is obvious and the Re is high, the drag influence of the nearest particle can represent the DNS result.